Side Docking: An Alternative Docking Method for Gynecologic Robotic Surgery - Einarsson, Jon I (MedReviews, LLC, 2011)
The authors propose an alternative method of robotic docking for gynecologic surgery. In this side-docking method, the robot is docked at an approximately 45° angle to the lower torso, aligned with the outer border of either the left or right stirrup, depending on the surgeon’s preference for left or right side-docking. The remainder of the patient and trocar setup is similar to traditional docking. The authors have had an excellent experience with this method as there does not seem to be an increased risk of robotic arm collision as long as the surgeon respects the basic principle of maintaining at least an 8- to 10-cm distance between each of the instrument ports. The significantly improved access to the vagina and perineum may facilitate robotically assisted gynecologic surgical procedures and reduce assistant fatigue and the potential for injury due to a collision with the robotic arms.